Industrial processes and waste stream management - Kumar, Vimal (SCITUS Academics LLC, 2016)
Waste management is largely regulated by legislation and policy implemented at the municipal level, but there are significant provincial regulations that may come into play. In some instances federal regulations may also be relevant, particularly if dealing with hazardous substances or shipping waste across provincial boundaries. Waste diversion and waste minimization are often a primary focus for most integrated waste management plans. Specific goals and targets are defined in a plan. In many jurisdictions, the ICI sector must follow prescribed federal, provincial and municipal goals and targets as identified in acts, regulations, and bylaws. The book lays the conceptual foundations with a detailed overview of waste stream management tools and regulations and the four EPA-approved treatment methods: physical, chemical, thermal, and biological. And provide a fascinating case-by-case exploration of industrial processes and how the waste streams they generate are managed in all major industries, including petroleum, chemicals, mining, metals, paint, textiles, agriculture, paper, printing, nuclear, medical, and more.